Defining Environmental Crime in International Law: Conceptual Ambiguities, Enforcement Gaps and Criminological Recognition - Mehwish Safdar; Sayyeda Fatima (ASIAN Journal of International Peace & Security (AJIPS), 2025)
Green crimes, a contemporary term for environmental crimes within green criminology, pose a significant threat to the planet. Numerous anthropogenic activities, illegal exploitation of natural resources, cases of corporate negligence and a range of wrongful and destructive acts against the nature remain unrecognized as crimes under international law. This gap primarily exists due to the lack of an adequate legal response from the international community to establish an internationally enforceable definition of environmental crimes. Consequently, crimes against the environment are often neglected and frequently escape prosecution owing to sovereignty concerns and inconsistent priorities. This article argues that the lack of a universal definition of environmental crime, legal ambiguities and enforcement deficiencies create critical enforcement gaps and institutional lacunae in the identification and prosecution of numerous harmful activities against the environment in international law. Through a doctrinal legal research design and the application of a green criminology framework, this article contends that the current international legal framework is insufficient. Therefore, to bridge the gap between environmental harm and accountability under international law, an interdisciplinary collaboration and development of coherent legal standards is crucial.